Training about Price Perception Optimization Strategy to Increase Consumer Satisfaction of Mie Gacoan among Students - Ummu Ufaizah Purba; Triya Harti Sholihat; Balqis Anisa Janati; Yenni Samri Juliati Nasution (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to identify and develop effective price perception optimization strategies to increase consumer satisfaction of Gacoan Noodles, especially among students of the State Islamic University of North Sumatra. In the face of intense competition in the culinary industry, appropriate pricing is an important factor in maintaining customer satisfaction and loyalty. This article uses Focus Group Discussion (FGD), training, and participatory methods to explore students' perceptions of the price and value of Mie Gacoan products. The results show that although the price of Mie Gacoan has been affordable, there is still a need to improve consumer perceptions related to product value. Therefore, additional education is needed through counseling and training related to price communication strategies. The training conducted succeeded in strengthening Mie Gacoan managers' understanding of how to maintain and improve consumers' positive perceptions of price, as well as managing consumer expectations to match the quality of the products offered. In addition, loyalty programs were also identified as an effective tool for building long-term relationships with consumers. Through the implementation of these strategies, Mie Gacoan is expected to significantly increase customer satisfaction and loyalty.